2023
DOI: 10.3390/jcm12216911
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune Inflammation Index as a Key Predictor of Dialysis in Pediatric Chronic Kidney Disease with the Use of Random Forest Classifier

Anna Kawalec,
Jakub Stojanowski,
Paulina Mazurkiewicz
et al.

Abstract: Background: Low-grade inflammation is a significant component of chronic kidney disease (CKD). Systemic immune inflammation index (SII), a newly defined ratio combining neutrophil, lymphocyte, and platelet counts, has not yet been evaluated in the pediatric CKD population nor in the context of CKD progression or dialysis. Thus, this study aimed to analyze the complete blood cell count (CBC)-driven parameters, including SII, in children with CKD and to assess their potential usefulness in the prediction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…As researchers have gradually recognized the importance of SII, an increasing number of reports have shown that SII is associated with many human health problems, such as hypertension ( 3 ), diabetes ( 4 ), and hyperlipidemia ( 5 ). The associations between SII and heart disease ( 6 ), kidney disease ( 7 ), and respiratory disease ( 8 ) have also been studied. As a relatively new marker of inflammation, much of the current research has focused on the relationship between SII and health problems, and research on the factors influencing SII is currently very limited.…”
Section: Introductionmentioning
confidence: 99%
“…As researchers have gradually recognized the importance of SII, an increasing number of reports have shown that SII is associated with many human health problems, such as hypertension ( 3 ), diabetes ( 4 ), and hyperlipidemia ( 5 ). The associations between SII and heart disease ( 6 ), kidney disease ( 7 ), and respiratory disease ( 8 ) have also been studied. As a relatively new marker of inflammation, much of the current research has focused on the relationship between SII and health problems, and research on the factors influencing SII is currently very limited.…”
Section: Introductionmentioning
confidence: 99%